Archery exploits of the Pharaohs - Loew, Rebecca Alice (My University, 2013)
Archery has been an important part of human history and Egypt is no exception. Several stories have been found detailing amazing archery feats of the pharaohs. By testing these stories we can learn more about the status of the pharaoh within Egyptian society as well as how truthful they were when talking about skills that could promote and reinforce their authority. In order to test these stories I have analyzed the archery equipment found within the tomb of Tutankhamun to determine modern day equivalents in order to be able to accurately determine if these stories are true, the result of bragging or a mixture of the two.
Keywords: Excavations (Archaeology); Archery; Archaeology - Methodology; Tutankhamen -- King of Egypt -- Tomb